2016
DOI: 10.1136/jmedgenet-2016-103839
|View full text |Cite
|
Sign up to set email alerts
|

PALB2,CHEK2andATMrare variants and cancer risk: data from COGS

Abstract: Background The rarity of mutations in PALB2, CHEK2 and ATM make it difficult to estimate precisely associated cancer risks. Population-based family studies have provided evidence that at least some of these mutations are associated with breast cancer risk as high as those associated with rare BRCA2 mutations. We aimed to estimate the relative risks associated with specific rare variants in PALB2, CHEK2 and ATM via a multicentre case-control study. Methods We genotyped 10 rare mutations using the custom iCOGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 35 publications
7
137
3
7
Order By: Relevance
“…These two studies [2, 3] together identified the p.Leu939Trp mutation in 10/1741 (0.57 %) women with breast cancer and 8/1534 (0.52 %) unaffected controls, suggesting that this mutation is not associated with breast cancer risk. Further, we later published a third study corroborating this null finding [4] and have subsequently reported additional evidence that the p.Leu939Trp mutation is not associated with breast cancer risk, based on genotyping of 42,671 breast cancer cases and 42,164 controls (odds ratio = 1.05, 95 % confidence interval = 0.83–1.32, p value = 0.70) [5]. Finally, we observed that the p.Leu939Trp mutation does not disrupt the HR-mediated DNA repair activity of PALB2 (Fig.…”
Section: Textmentioning
confidence: 91%
“…These two studies [2, 3] together identified the p.Leu939Trp mutation in 10/1741 (0.57 %) women with breast cancer and 8/1534 (0.52 %) unaffected controls, suggesting that this mutation is not associated with breast cancer risk. Further, we later published a third study corroborating this null finding [4] and have subsequently reported additional evidence that the p.Leu939Trp mutation is not associated with breast cancer risk, based on genotyping of 42,671 breast cancer cases and 42,164 controls (odds ratio = 1.05, 95 % confidence interval = 0.83–1.32, p value = 0.70) [5]. Finally, we observed that the p.Leu939Trp mutation does not disrupt the HR-mediated DNA repair activity of PALB2 (Fig.…”
Section: Textmentioning
confidence: 91%
“…The risk is particularly high in women with rare high-penetrance sequence variants, such as mutations in BRCA1 or BRCA2, where the 10-year risk may approach 25% to 30% (4,5). Mutations in CHEK2 also increase the risk of CBC, albeit to a lesser degree (6,7), and rare pathogenic PALB2 mutations have also been shown to increase the risk of CBC (8,9). In some family studies and within subgroups of breast cancer patients, rare mutations in the ATM gene have also been shown to increase the risk of CBC (10,11).…”
mentioning
confidence: 99%
“…mutations descending from a single ancestor have been described for example in genes causing familial breast cancer. [47][48][49][50][51] Chondrocytic cell lines were not available for the predictions of the promoter and enhancer regions. Instead data from HSMM and GM12878 cell lines were used.…”
Section: Discussionmentioning
confidence: 99%